Interaction of 137Cs with Sumedang Clay as Natural Barrier of Radwaste Disposal - B. Setiawan; U. Zhafirah; A. Saefumillah (Atom Indonesia, 2019)
The interaction of 137Cs with Sumedang clay as a natural barrier for radwaste disposal system has been studied. The initial concentration of Cs was 10‑8 M for the experiments on the contact time and the effect of Na and K concentrations on the sorption of 137Cs; however, the initial concentration ranging from 10‑8 to 10‑3 M of CsCl in the solution for the effect of CsCl concentration. The distribution coefficient Kd is used as the indicator of 137Cs sorption into samples. It was found that the Kd values decreased nonlinearly with the concentration of Na and K, and also to the effects of CsCl concentration. A Freundlich isotherm was proposed to explain the sorption phenomena observed in the experiment. Conclusion of the experiments shown that the presence of metal ions such as Na+ and K+ and variation of CsCl concentrations in the solution have a significant effect on the sorption of 137Cs to the samples. The results should be taken into account for the assessment or selection of the site of radwaste disposal facility in the future.